Analyzing change in international politics: The new institutionalism and the interpretative approach - Peter Joachim Katzenstein (Max-Planck-Institut für Gesellschaftsforschung, 1990)
This paper argues that realism misinterprets change in the international system. Realism conceives of states as actors and international regimes as variables that affect national strategies. Alternatively, we can think of states as structures and regimes as part of the overall context in which interests are defined. States conceived as structures offer rich insights into the causes and consequences of international politics. And regimes conceived as a context in which interests are defined offer a broad perspective of the interaction between norms and interests in international politics. The paper concludes by suggesting that it may be time to forego an exclusive reliance on the Eurocentric, Western state system for the derivation of analytical categories. Instead we may benefit also from studying the historical experience of Asian empires while developing analytical categories which may be useful for the analysis of current international developments. – – In diesem Aufsatz wird argumentiert, daß der realistische Ansatz außenpolitischer Theorie Wandel im internationalen System fehlinterpretiere. Dieser versteht Staaten als Akteure und internationale Regime als Variablen, die nationale Strategien beeinflussen. Alternativ kann man Staaten als Strukturen und Regime als Teile eines übergreifenden Kontextes begreifen, innerhalb dessen Interessen definiert werden. Wenn Staaten als Strukturen aufgefaßt werden, ergeben sich vielfältige Einsichten in die Ursachen und Wirkungen internationaler Politik. Und Regime, konzipiert als Kontexte, in denen sich Interessen konstituieren, eröffnen einen breiten Einblick in die Interaktion zwischen Normen und Interessen im Bereich internationaler politischer Prozesse. Das Papier schließt mit der Empfehlung, analytische Kategorien nicht mehr ausschließlich aus der Betrachtung des eurozentrischen, westlichen Staatensystems zu entwickeln. Vielmehr erscheint es fruchtbar, auch die historische Entwicklung asiatischer Reiche zu untersuchen, um Kategorien für die Analyse gegenwärtiger internationaler Entwicklungen zu gewinnen.
Keywords: 300